2018
DOI: 10.1530/rep-17-0617
|View full text |Cite
|
Sign up to set email alerts
|

The C-X-C signalling system in the rodent vs primate testis: impact on germ cell niche interaction

Abstract: In zebrafish, action of the chemokine Cxcl12 is mediated through its G-protein-coupled seven-transmembrane domain receptor Cxcr4 and the atypical receptor Cxcr7. Employing this animal model, it was revealed that this Cxcl12 signalling system plays a crucial role for directed migration of primordial germ cells (PGC) during early testicular development. Importantly, subsequent studies indicated that this regulatory mechanism is evolutionarily conserved also in mice. What is more, the functional role of the CXCL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Within the testis, a special situation may exist, since MIF is a ligand for the CXCR4, expressed by SSCs, and is essential for postnatal maintenance of the SSCs in marmosets and mice 57 . If indeed applicable to the testis, higher levels of MIF may influence the SSC niche via CXCR4 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Within the testis, a special situation may exist, since MIF is a ligand for the CXCR4, expressed by SSCs, and is essential for postnatal maintenance of the SSCs in marmosets and mice 57 . If indeed applicable to the testis, higher levels of MIF may influence the SSC niche via CXCR4 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we described an important role of CXCR4 in mouse SSC maintenance [22]. Interestingly, recent studies reported that CXCR4 + cells contained enriched SSC activity in bull, boar and human testis [32, 43, 44] . Findings from the current study demonstrated that CXCR4 was only expressed in gonocytes and a small number of spermatogonia; we therefore proposed that CXCR4 can be used as a marker for SSC enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…As a chemokine involved in the regulation of tissue stem cells, the previous analyses of CXCL12 have been impressive. CXCL12, through its receptor CXCR4, is responsible for the maintenance and differentiation of tissue stem cells, such as bone marrow hematopoietic stem cells, primordial germ cells, and neural stem cells, in the stem cell niche of the tissue microenvironment [ 56 , 57 , 58 ]. This function may be mainly based on the chemoattractant activity of CXCL12 toward the stem cell niche.…”
Section: Discussionmentioning
confidence: 99%